Analisis SWOT pada kegiatan penangkaran penyu di Batavia Bangka Beach, Sungailiat Bangka - Umroh Umroh; Suci Puspita Sari; Laksita Aria Kusuma (Jurusan Akuakultur, Universitas Bangka Belitung, 2014)
The turtle breeding activities at Batavia Bangka Beach was one of the shelter efforts to rescue the turtle’s eggs at the beach, to grow it up and to release them into the sea. The aim of this research were to find some internal and external factors on the turtle breeding activities at Batavia Bangka Beach and to decide the supervision strategies to the turtle breeding activities at Batavia Bangka Beach based on their internal and external factors analysis. Descriptive method supported by primer and secondary data. The collection of the data was run from May to September 2011. There were eight internal and seven external factors found affecting the turtle breeding activities at Batavia Bangka Beach. SWOT analysis revealed that the strategy of the turtle breeding activities at Batavia Bangka Beach was Strength-Threat (ST) strategy. The existing turtle breeding activities at Batavia Bangka Beach were in unprofitable state; so that, ST strategy should be the priority.